2022
DOI: 10.1111/desc.13316
|View full text |Cite
|
Sign up to set email alerts
|

Preschool language and visuospatial skills respectively predict multiplication and addition/subtraction skills in middle school children

Abstract: A converging body of evidence from neuroimaging, behavioral, and neuropsychology studies suggests that different arithmetic operations rely on distinct neuro-cognitive processes: while addition and subtraction may rely more on visuospatial reasoning, multiplication would depend more on verbal abilities. In this paper, we tested this hypothesis in a longitudinal study measuring language and visuospatial skills in 358 preschoolers, and testing their mental calculation skills at the beginning of middle school. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Multiplication may dissociate from other operations because it is usually learned in ways that emphasize verbal rote learning to a greater extent than other operations, and thus may rely more than other operation on verbal skills. Guez et al (2023) carried out a longitudinal study of 358 American children from preschool (5; 5 years) to age 11. They found that preschool language skills, but not visuospatial skills, predicted multiplication skills at age 11, whereas preschool visuospatial skills, but not language skills, predicted addition and subtraction skills at age 11.…”
Section: Domain-general Abilitiesmentioning
confidence: 99%
“…Multiplication may dissociate from other operations because it is usually learned in ways that emphasize verbal rote learning to a greater extent than other operations, and thus may rely more than other operation on verbal skills. Guez et al (2023) carried out a longitudinal study of 358 American children from preschool (5; 5 years) to age 11. They found that preschool language skills, but not visuospatial skills, predicted multiplication skills at age 11, whereas preschool visuospatial skills, but not language skills, predicted addition and subtraction skills at age 11.…”
Section: Domain-general Abilitiesmentioning
confidence: 99%
“…Visuospatial skills accordingly predict subtraction, but not multiplication operations. Language skills inversely predict multiplication but not subtraction ( Lee and Kang, 2002 ; Guez et al, 2022 ). At the neural level, subtraction has been linked to an increased activity of the parietal cortex, typically associated with quantity and visuospatial processing.…”
Section: Introductionmentioning
confidence: 99%
“…Multiplication appears to be more dependent on language than other arithmetical operations, probably because it is usually taught in a way that places greater emphasis on verbal memorisation. Guez, Piaz, Pinheiro-Chagas, et al [ 89 ] found that preschool children’s language skills, but not their visuospatial skills, predicted their multiplication performance at the age of 11. In contrast, their visuospatial skills, but not their language skills, predicted their addition and subtraction performance at the age of 11.…”
Section: Introductionmentioning
confidence: 99%